Evaluation of rhodamine b photocatalytic degradation over batio3-mno2 ceramic materials - Kuźniarska-Biernacka, Iwona; Garbarz-Glos, Barbara; Skiba, Elzbieta; Maniukiewicz, Waldemar; Bak, Wojciech; Antonova, Maija; Rebelo, Susana L. H.; Freire, Cristina (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Ferroelectric ceramics (BaTiO3_MnO2 ) with different Mn admixtures were prepared using solid-state synthesis. Elemental analysis, powder X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy, and impedance spectroscopy confirmed that the BaTiO3 and MnO2 coexisted in the ceramics. In addition, the high purity and homogeneity of the element distributions in the ceramic samples were confirmed. The adsorptive and photocatalytic properties of the BaTiO3 (reference sample, BTO) and BaTiO3_MnO2 materials (BTO_x, where x is wt.% of MnO2 and x = 1, 2 or 3, denoted as BTO_1, BTO_2 and BTO_3, respectively) were evaluated using Rhodamine B (RhB) as the model dye in a photocatalytic chamber equipped with a UV lamp (15 W) in the absence of additional oxidants and (co)catalysts. No adsorption of RhB dye was found for all the materials during 360 min (dark experiment). All samples were photocatalytically active, and the best results were observed for the BTO_3 material, where RhB was 70% removed from aqueous solution during 360 min of irradiation. The photodegradation of RhB in the presence of MnO2-modified BTO ceramics followed a pseudo-first order model and the rate constant of BTO_3 was about 10 times higher than that of BTO, 2 times that of BTO_2, and 1.5 times that of BTO_1. The photocatalysts could be successfully reused after thermal activation. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Published under the CC BY 4.0 license.
This research was funded by UIDB/50006/2020 with funding from FCT/MCTES through national funds and from the Institute of General and Ecological Chemistry of Lodz University of Technology. Susana L.H. Rebelo and Iwona Kuźniarska-Biernacka thank FCT (Fundação para a Ciência e Tecnologia) for funding through program DL 57/2016–Norma transitória (RE-QUIMTE/EEC2018/30 (SLHR) and REQUIMTE/EEC2018/14 (IKB)).
Keywords: Research Subject Categories::NATURAL SCIENCES; Impedance spectroscopy; Perovskite; Photo-oxidation; Photocatalysts; Water treatment